The Effect of Dehydroepiandrosterone on Ovarian Reserve in Ovarian Damage Caused by Methotrexate - Ali Doğukan Anğın; Ebru Çöğendez; İsmet Gün; Önder Sakin; Muzaffer Seyhan Çıkman; Kayhan Başak; Asuman Orçun Kaptanağası; Yasemin Alan; Murat Alan; Emrah Beyan (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
To determine the possible detrimental effects of multiple methotrexate doses has on the ovarian reserve and to determine the beneficial effects of dehydroepiandrosterone supplementation. The rats (n:24) divided into three groups; Group 1: control group, Group 2: dehydroepiandrosterone and methotrexate group (6mg/kg dehydroepiandrosterone dissolved in 0.1 ml sesame seed oil subcutaneously for ten days and 1mg/kg intramuscular methotrexate at the 1st, 3rd, 5th and 7th days) and Group 3: methotrexate group (1mg/kg intramuscular methotrexate at the 1st, 3rd, 5th and 7th day). The groups compared in regards to their histopathological ovarian damage scores and AMH values. It established that multiple methotrexate applications had a considerable effect on reducing vascular congestion in the ovarian tissue. Both in groups 2 and 3 AMH values found to be significantly lower. When this decline in the ovarian reserve examined comparatively; while both the group 2 and 3 reported having a considerable and continuous reduction in the AMH levels correlative to the control group; the primordial, primary and total follicle counts shown to stay statistically the same in the group 2 (p